(untitled) (Iranian Journal of Kidney Diseases, 2023)
Fabry disease (FD) is a multi-organ disorder caused by a deficiency of alpha-galactosidase (α-GLA) or reduced activity of the enzyme due to mutations in the GLA gene on the X chromosome, making it an X-linked hereditary disease. A 37-year-old man previously diagnosed with sudden deafness and cardiac hypertrophy was referred to our department after an abnormal urine finding during a public health checkup. A renal biopsy revealed characteristic findings, and he was diagnosed with FD with a novel GLA abnormality (c.714dupT (p.I239Yfs*11)). We are currently administering enzyme replacement therapy (ERT) with agalsidase α. This case shows that a novel genetic abnormality in FD can be overlooked for 37 years, even in the presence of typical symptoms. The significance of a renal biopsy in diagnosing FD is emphasized, highlighting the crucial role of nephrologists. DOI: 10.52547/ijkd.7595